Teacher performance and student fitness: is there a significant relationship? - Bella Shasi Saraswara; Ali Maksum; Advendi Kristiyandaru; Muhammad Labib Siena Ar Rasyid (Journal Of Sport Education (JOPE), 2024)
(English)This research aims to reveal the level of PF of students in ten JHS based on the results of PE teachers' performance based on four competencies. Fitness of JHS students in the city of Pekanbaru and the influence of PE teacher performance on fitness student physical. An Ex Post Facto approach was used in this survey research. The instrument to see the performance of PE teachers is to use a questionnaire. Meanwhile, to measure students' PF, the test used is the bleep test. The principal, deputy principal for public relations, deputy principal for curriculum, and one student in class VIII (eight) whose physical fitness data was taken randomly from each school were used as samples in this study. The results of this research include: (1) the performance of JHS PE teachers in Pekanbaru City has met expectations because the four competencies are in the very good category, where personality competency has the highest percentage, (2) Lack of PA inside and outside school will causes low PF of students (Vo2Max), (3) From the results of the regression test which shows a figure of 14.3%, it shows that the high quality of PE teachers' performance does not have a direct impact on students' PF. The conclusion of this research is that the competence of PE teachers does not have a significant impact on students' PF levels because there are other factors that influence it, such as the level of active participation of students inside and outside school. These findings recommend, among other things: (1) the need for consistency in the quality of PE teachers and the professionalism of teachers in schools, (2) the need to maintain the quality of students' PF to improve the quality of life, (3) the need to determine or select PE materials that are adapted to the characteristics of children so that students can be more active in the learning process so that the goals of PE are achieved. (Indonesian)Penelitian ini bertujuan untuk mengungkap tingkat kebugaran jasmani siswa di sepuluh sekolah menengah pertama didasarkan pada hasil kinerja guru pendidikan jasmani berdasarkan empat kompetensi. kebugaran siswa sekolah menengah pertama di kota Pekanbaru dan pengaruh kinerja guru pendidikan jasmani terhadap kebugaran. fisik siswa.  Pendekatan Ex Post Facto digunakan dalam penelitian survei ini. Instrumen untuk melihat kinerja guru pendidikan jasmani adalah dengan menggunakan angket. Sedangkan untuk mengukur kebugaran jasmani siswa, tes yang digunakan adalah bleep test.  Kepala sekolah, wakil kepala sekolah bidang humas, wakil kepala sekolah bidang kurikulum, satu siswa kelas VIII (delapan) yang data kebugaran jasmaninya diambil secara acak disetiap sekolah dijadikan sampel dalam penelitian ini. Hasil penelitian ini antara lain: (1) kinerja guru pendidikan jasmani JHS di Kota Pekanbaru sudah memenuhi harapan karena keempat kompetensi berada pada kategori sangat baik, dimana kompetensi kepribadian mempunyai persentase paling tinggi, (2) Kurangnya aktivitas fisik di dalam dan di luar sekolah akan menyebabkan rendahnya kebugaran jasmani siswa (Vo2Max), (3) Dari hasil uji regresi yang menunjukkan angka 14,3% menunjukkan tingginya kualitas kinerja guru penjas tidak berdampak langsung terhadap kebugaran jasmani siswa. Kesimpulan dari penelitian ini adalah kompetensi guru PE tidak berdampak secara signifikan terhadap tingkat kebugaran jasmani siswa karena ada faktor lain yang mempengaruhinya seperti tingkat partisipasi aktif siswa di dalam maupun luar sekolah. Temuan tersebut merekomendasikan antara lain: (1) diperlukan konsistensi kualitas guru pendidikan jasmani dan profesionalitas guru di sekolah, (2) perlunya menjaga kualitas kebugaran jasmani siswa untuk meningkatkan kualitas hidup, (3) perlunya menetapkan atau memilih materi pendidikan jasmani yang disesuaikan dengan karakteristik anak sehingga siswa dapat lebih aktif dalam proses pembelajaran sehingga tujuan pendidikan jasmani tercapai.Copyright © The Author (s) 2024Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.